The 5 levels of leadership : proven steps to maximise your potential - Maxwell, John C., 1947-; Center Street School (Mentor, Ohio) (New York : Center Street, 2011)
MANAGEMENT and MANAGEMENT TECHNIQUES. One of the most established authorities on leadership writing today, John C. Maxwell, shares the five stages of leadership and how to maximise each.
Keywords: Leadership